PENGARUH AKSESIBILITAS, FASILITAS, DAN DAYA TARIK WISATA TERHADAP MINAT BERKUNJUNG KEMBALI WISATAWAN DI PANTAI TEMBERAN KABUPATEN BANGKA - Septari Hikmawati; Sumar; Darman Saputra (PT. Hasba Edukasi Mandiri, 2025)
Tourism has become one of the industries capable of accelerating economic growth. This is evident from its role in providing employment, increasing income and living standards, and stimulating other productive sectors, making tourism a vital contributor to Indonesia's economy. This study aims to analyze and determine the influence of accessibility, facilities, and tourist attractions on tourists' revisit intention to Temberan Beach, Bangka Regency. A quantitative approach was used, involving 100 respondents selected through purposive sampling. The independent variables in this study are accessibility, facilities, and tourist attractions, while the dependent variable is revisit intention. Data were processed using multiple linear regression analysis with t-tests, F-tests, and the coefficient of determination (R²). The results of the multiple linear regression analysis yielded the equation: Y = 1.732 + 0.705X₁ + 0.472X₂ + 0.666X₃. Partially, the variables of accessibility and tourist attractions have a positive and significant effect on revisit intention, while the facilities variable has a positive but not significant effect. Simultaneously, accessibility, facilities, and tourist attractions have a positive and significant influence on tourists' revisit intention to Temberan Beach. The coefficient of determination (R²) is 88.9%, indicating that the variables studied explain 88.9% of the variation in revisit intention, with the remaining 11.1% influenced by other factors not included in this study.